(untitled) (INNOVATIVE ECONOMY, 2020)
Neboha T.V. STRATEGIC MANAGEMENT OF INNOVATIVE DEVELOPMENT OF INFOCOMMUNICATION SPHERE AS A FACTOR OF MODERNIZATION OF NATIONAL INNOVATIVE INFRASTRUCTURE Purpose. The aim of the article is to substantiate the scientific and theoretical bases of formation mechanism of strategic management of innovative development of infocommunication sphere as a factor of innovation and modernization of infrastructure of the national economy. Methodology of research. General scientific methods are used in the process of the study, namely: methods of theoretical generalization - to study the mechanism of strategic management of innovative infrastructure development of infocommunication sphere; a systematic approach to support the strategic priority directions of innovative development of sphere of information and communication technologies; methods of analysis and synthesis – to determine the set of activities necessary to achieve the represented strategic directions of innovative development of sphere of Infocommunications. Findings. The mechanism of strategic management of innovative infrastructure development of infocommunication sphere is investigated. Strategic priority directions of innovative development of the infocommunication sphere are substantiated. The complex of necessary measures to achieve the presented strategic directions of innovative development of the infocommunication sphere is determined. Originality. Scientific and theoretical bases of formation mechanism of strategic management of innovative infrastructure development of infocommunication sphere as a factor of innovation and modernization of infrastructure of the national economy is developed. It consists of three modules: forecasting and analytical, of intensification-oriented and certification, the implementation of which contributes to the intensification of innovative processes in all spheres of economic activities and innovative infrastructure development of the national economy. Practical value. The results of research are aimed at solving problems of strategic management of innovative infrastructure development of infocommunication sphere as part of the innovation infrastructure of the national economy and can be applied in the development of a national strategy for the development of information and communication sphere. Key words: ICT sector, innovative infrastructure, national economy, management strategy, innovative development.